2021
DOI: 10.1177/15570851211062577
|View full text |Cite
|
Sign up to set email alerts
|

Can Respectful Employees Create Equitable Institutions? Promoting a Culture of Respect in the Higher Education Workplace

Abstract: This paper describes challenges to changing the culture around yellow zone sexual harassment in the higher education workplace. The yellow zone comprises harassment that is often undetected or misunderstood but nonetheless is harmful. Based on a random sample, we surveyed 4554 staff and faculty at a large Midwestern university after they completed a mandatory online training module, assessing perceptions of sexual harassment, reactions to the training, and workplace personal experiences. Findings are that a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Similarly, Rubino et al [ 31 ] found that sexual harassment is less frequent and, when it occurs, has a lesser impact when greater organizational justice is perceived. Robotham and Cortina [ 32 ], Banner et al [ 33 ], and Lim and Cortina [ 34 ] found that a climate of respect is a protective factor against workplace sexual harassment. Perry et al [ 35 ] proposed that inclusive leadership can promote an environment of respect, making WSH less likely.…”
Section: Proposed Modelmentioning
confidence: 99%
“…Similarly, Rubino et al [ 31 ] found that sexual harassment is less frequent and, when it occurs, has a lesser impact when greater organizational justice is perceived. Robotham and Cortina [ 32 ], Banner et al [ 33 ], and Lim and Cortina [ 34 ] found that a climate of respect is a protective factor against workplace sexual harassment. Perry et al [ 35 ] proposed that inclusive leadership can promote an environment of respect, making WSH less likely.…”
Section: Proposed Modelmentioning
confidence: 99%
“…Indicators for improving workplace lifestyle include job satisfaction, involvement in work, the right to express opinions, reduction of workplace accidents and incidents, the right to choose one's profession, destiny, influence, and more. Ignoring the improvement of workplace lifestyle means that employees regard their jobs merely as a means to satisfy economic needs, and such employees generally show low loyalty to the organization and often need to engage in other activities to compensate for deficiencies (Banner et al, 2021;Susomrith & Coetzer, 2019).…”
mentioning
confidence: 99%